CuA-based chimeric T1 copper sites allow for independent modulation of reorganization energy and reduction potential - Szuster, Jonathan (2021)
Fil: Fil: Szuster, Jonathan. Universidad de Buenos Aires. Instituto de Química Física de los Materiales, Medio Ambiente y Energía (INQUIMAE -CONICET); Argentina.